4(6-3v)=6v-66

Simple and best practice solution for 4(6-3v)=6v-66 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(6-3v)=6v-66 equation:



4(6-3v)=6v-66
We move all terms to the left:
4(6-3v)-(6v-66)=0
We add all the numbers together, and all the variables
4(-3v+6)-(6v-66)=0
We multiply parentheses
-12v-(6v-66)+24=0
We get rid of parentheses
-12v-6v+66+24=0
We add all the numbers together, and all the variables
-18v+90=0
We move all terms containing v to the left, all other terms to the right
-18v=-90
v=-90/-18
v=+5

See similar equations:

| 4x+10=2(x-8) | | −23x–214=274x= | | 43−27=d | | 17+y=48 | | 4x–10=–42 | | 30÷a=6 | | 5-4+7x+1=6x-2 | | 5-4+7x+1=9x-4 | | 5-4+7x+1=3x+0 | | 10a-7=24 | | 100-c/2=35 | | .(b+12)2=81 | | (x+12)2=81 | | -3x^2+5=-37 | | 21÷a=7 | | -3x^2=32 | | x+(x+2)-4=90 | | 1.13x=15 | | t+3=-12 | | 6p+2p=28 | | 4x-9=-111-8x | | a=−6 | | z/5+1=9 | | 4-(3x-5)=6-(2x+7 | | 19+2x+x=40 | | 7(4s+6)=378 | | y-16=27 | | -4(3d-1)+2(7d=9) | | 4x-8=4x+-16 | | 0.7*x+x=100 | | x+20=5x-2 | | 4x+-8=4x+0 |

Equations solver categories